Pengolahan Air Limbah Industri Pulp dengan Metode Oksidasi Elektrokimia Termediasi - Haryono,; Juliandri,; Evy Ernawati, (ReTII, 2023)
The pulp industry processes natural organic materials, especially compounds in the lignocellulosic group, by utilizing various types of chemicals. Therefore, the pulp industry has the potential to produce hazardous and toxic liquid waste with a relatively dark color. Mediated Electrochemical Oxidation (MEO) can be applied to treat the wastewater from the pulp industry. The MEO method allows organic compounds in wastewater to be mineralized into carbon dioxide and water. The purpose of this study was to determine the effect of the potential difference between graphite electrodes and the volume of sodium hypochlorite solution as a mediator on the efficiency of mineralization and the reduction of color intensity from pulp industry wastewater. The potential difference between the electrodes is varied at 4.5; 6.0; and 7.5 volts, while the volume of the mediator was studied at variations of 50 and 100 mL. The results showed that the highest mineralization efficiency was achieved at 82.5% when electrolysis of the MEO cell was carried out at a voltage difference of 7.5 volts and a mediator volume of 100 mL, while the highest decrease in color intensity was achieved at a cell potential difference of 4.5 volts and a mediator volume of 100 mL, with a decrease in color intensity of 61.61%.